Comparison of two delayed strategies for renal replacement therapy initiation for severe acute kidney injury (AKIKI 2): a multicentre, open-label, randomised, controlled trial. Issue 10281 (3rd April 2021) - Gaudry, Stéphane; Hajage, David; Martin-Lefevre, Laurent; Lebbah, Saïd; Louis, Guillaume; Moschietto, Sébastien; Titeca-Beauport, Dimitri; Combe, Béatrice La; Pons, Bertrand; de Prost, Nicolas; Besset, Sébastien; Combes, Alain; et al.
Summary: Background: Delaying renal replacement therapy (RRT) for some time in critically ill patients with severe acute kidney injury and no severe complication is safe and allows optimisation of the use of medical devices. Major uncertainty remains concerning the duration for which RRT can be postponed without risk. Our aim was to test the hypothesis that a more-delayed initiation strategy would result in more RRT-free days, compared with a delayed strategy. Methods: This was an unmasked, multicentre, prospective, open-label, randomised, controlled trial done in 39 intensive care units in France. We monitored critically ill patients with severe acute kidney injury (defined as Kidney Disease: Improving Global Outcomes stage 3) until they had oliguria for more than 72 h or a blood urea nitrogen concentration higher than 112 mg/dL. Patients were then randomly assigned (1:1) to either a strategy (delayed strategy) in which RRT was started just after randomisation or to a more-delayed strategy. With the more-delayed strategy, RRT initiation was postponed until mandatory indication (noticeable hyperkalaemia or metabolic acidosis or pulmonary oedema) or until blood urea nitrogen concentration reached 140 mg/dL. The primary outcome was the number of days alive and free of RRT between randomisation and day 28 and was done in the intention-to-treat population. The study is registered with ClinicalTrial.gov, NCT03396757 and is completed. Findings: Between May 7, 2018, and Oct 11, 2019, of 5336 patients assessed, 278 patients underwent randomisation; 137 were assigned to the delayed strategy and 141 to the more-delayed strategy. The number of complications potentially related to acute kidney injury or to RRT were similar between groups. The median number of RRT-free days was 12 days (IQR 0–25) in the delayed strategy and 10 days (IQR 0–24) in the more-delayed strategy (p=0·93). In a multivariable analysis, the hazard ratio for death at 60 days was 1·65 (95% CI 1·09–2·50, p=0·018) with the more-delayed versus the delayed strategy. The number of complications potentially related to acute kidney injury or renal replacement therapy did not differ between groups. Interpretation: In severe acute kidney injury patients with oliguria for more than 72 h or blood urea nitrogen concentration higher than 112 mg/dL and no severe complication that would mandate immediate RRT, longer postponing of RRT initiation did not confer additional benefit and was associated with potential harm. Funding: Programme Hospitalier de Recherche Clinique.